The access of researchers from developing countries to international science and technology (2002)
Different problems of access to scientific knowledge by researchers from developing countries are surveyed. Obstacles are classified according to their source: those inherent to research processes in general and having special inhibitory effects on researchers from developing countries, and those related to the institutional framework and economic environment of the developing country itself. The trend towards privatisation of scientific results has led many open-science institutions in industrialised countries to restrict access to the knowledge they use and produce. Nonetheless, the inability of scientific and technological communities of developing countries to endogenise economic and political support for their activities is presented as the main obstacle for their access to knowledge. Insufficient resources for research, even in countries that could easily allocate important funds for these activities, are shown to be an important obstacle in a world where scientific and technological information is increasingly marketed and expensive. The dynamics leading to a low efficiency equilibrium of scientific and technological activities are characterised.